2010
DOI: 10.1111/j.1365-2915.2010.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification of two Brazilian triatomes, Triatoma arthurneivai and Triatoma wygodzinskyi, revealed by geometric morphometrics

Abstract: Triatoma arthurneivai Lent & Martins and Triatoma wygodzinskyi Lent (Hemiptera: Reduviidae) are two Brazilian species found in the sylvatic environment. Several authors may have misidentified T. arthurneivai and consequently published erroneous information. This work reports the use of geometric morphometric analysis on wings in order to differentiate T. arthurneivai and T. wygodzinskyi, and thus to detect possible misidentifications. Triatomines collected from the field in the states of Minas Gerais and São P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…Curiosidades: recentes análises morfométricas publicadas por Carbajal de la Fuente et al (2010) demonstraram que espécimes dessa espécie, provenientes de São Paulo, foram erroneamente identificados como T. arthurneivai gerando cerca de uma dezena de publicações dedicadas a T. arthurneivai nas quais a espécie estudada foi, de fato, T. wygodzinskyi. (Cleber Galvão & Carolina Dale) Neste capítulo são apresentadas chaves dicotômicas pictóricas atualizadas para todas as tribos e gêneros da subfamília Triatominae.…”
Section: Habitat: Sob Pedrasunclassified
“…Curiosidades: recentes análises morfométricas publicadas por Carbajal de la Fuente et al (2010) demonstraram que espécimes dessa espécie, provenientes de São Paulo, foram erroneamente identificados como T. arthurneivai gerando cerca de uma dezena de publicações dedicadas a T. arthurneivai nas quais a espécie estudada foi, de fato, T. wygodzinskyi. (Cleber Galvão & Carolina Dale) Neste capítulo são apresentadas chaves dicotômicas pictóricas atualizadas para todas as tribos e gêneros da subfamília Triatominae.…”
Section: Habitat: Sob Pedrasunclassified
“…Therefore, the combination of cytotaxonomic and morphometric analyses (Carbajal de la Fuente et al, 2011) were proven to be of utmost taxonomic and epidemiological importance for the identification of T. arthurneivai and T. wygodzinskyi specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent geometric morphometric study showed that the insects captured outside the Serra do Cipó region were T. wygodzinskyi specimens (Carbajal de la Fuente et al, 2011). These authors reported that the populations of T. arthurneivai from São Paulo, which were studied for more than 40 years by several authors (Corrêa et al, 1962(Corrêa et al, , 1965Pinto Alves and Noda, 1964;Juarez, 1970;Forattini et al, 1968Forattini et al, , 1972Barretto and Ribeiro, 1981;Hypsa et al, 2002;de Paula et al, 2005;Rosa et al, 2005;Dos Santos et al, 2007;Bargues et al, 2008), were actually T. wygodzinskyi specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Panzera et al (2010) describe the pattern heterochromatic of T. wygodzinskyi as identical to that observed for T. arthurneivai. However, Carbajal-de-La-Fuente et al (2010) highlight that in many works of literature T. wygodzinskyi was erroneously classified as T. arthurneivai. Thus, this work describes the heterochromatic pattern of all species of the Maculata subcomplex, with cytotaxonomic focus.…”
Section: Scientific Notementioning
confidence: 90%